From toxicity assessment to adaptive safety care: implementing comprehensive fast-track safety evaluation for anticancer drug development - Champiat, Stéphane; Ouali, Kaissa; Laparra, Ariane; Charalambous, Andreas; Di Palma, Mario; Jordan, Karin; Massard, Christophe; Aapro, Matti; Scotte, Florian (Elsevier BV, 2026)
Background
The conventional drug development pathway in oncology, spanning 10-15 years, has long been slow, costly, and complex, often marked by late-stage failures due to efficacy or safety concerns.
Materials and methods
We aimed to develop this position paper, based on a literature review and by sharing experience, skills, and works of the different co-authors, in order to propose a new approach to the clinical trials’ process.
Results
In the past decade, the field has undergone major transformation. Innovative trial designs and fast-track regulatory pathways, such as priority review, breakthrough designation, accelerated approval, and fast-track processes, have significantly shortened timelines from phase I to market approval. While these approaches have enabled quicker access to promising therapies, they have also exposed gaps in postmarketing safety and highlighted the need for tailored adverse event management strategies. These emerging safety challenges call for multidisciplinary evaluation and the integration of advanced monitoring technologies.
Conclusions
This manuscript introduces a comprehensive, adaptive fast-track safety evaluation framework designed to support oncology drug development. It aims to enhance patient safety while preserving the benefits of accelerated regulatory pathways.